Galaxies Lighting Up: Discovery of Seventy New Turn-on Changing-look Active Galactic Nuclei - Qian Yang; Paul J. Green; Xue-Bing Wu; Michael Eracleous; Linhua Jiang; Yuming Fu (The Astrophysical Journal)
“Changing-look active galactic nuclei” (CL AGN) show dramatic, rapid changes in optical/UV continuum and broad-line emission. The majority of CL AGN have been found dimming as “turn-off” CL AGN because most selection methods start from samples of spectroscopically confirmed quasars. We present here a sample of 82 spectroscopically confirmed “turn-on” CL AGN, 70 of which are newly identified. The turn-on CL AGN are selected from spectroscopically classified galaxies with subsequent significant and dramatic variability in both the optical and mid-infrared bands, indicating a mechanism of changing accretion rate of the supermassive black holes (BHs) rather than variable obscuration. Based on their bright state Eddington ratios, turn-on CL AGN are associated with lower accretion rates compared to turn-off CL AGN or typical Sloan Digital Sky Survey quasars with similar redshift and magnitude distributions, even though turn-on CL AGN have lower BH masses. Most turn-on CL AGN reside in host galaxies that follow local relations between the central BH mass and host galaxy properties, such as stellar mass and velocity dispersion. However, their host galaxies have higher mass than normal inactive galaxies, with star formation rates more similar to hosts of Type 2 AGN than to the overall galaxy population.